Meet the expert : Marc Stickdorn on service design. (O'Reilly Media, Inc., 2020)
"In this edition of Meet the Expert with Marc Stickdorn, author of This Is Service Design Doing and This Is Service Design Methods, learn how to embed and scale service design in-house, use journey maps as a visual management tool for Agile organizations, and use service design to enhance employee experiences. Marc outlines 10 trends and recent developments in service design from around the world and shares tips on how to conduct service design with remote teams-particularly useful during the current global crisis. Recorded on July 22, 2020"--Resource description page